Biological, biochemical and molecular aspects of Scedosporium aurantiacum, a primary and opportunistic fungal pathogen. Issue 3 (June 2018) - Nevalainen, Helena; Kaur, Jashanpreet; Han, Zhiping; Kautto, Liisa; Ramsperger, Marc; Meyer, Wieland; Chen, Sharon C.-A.
Abstract: The present review summarises the current knowledge of the biology, biochemistry and molecular aspects of S. aurantiacum in context with the broader knowledge on Scedosporium spp, generated over the past decade. Recently, the genus has undergone two taxonomical reviews. S. aurantiacum is widely distributed in all ecological niches and geographical locations. It is a highly pathogenic opportunist capable of causing a broad range of diseases via infections occurring in the lungs, sinuses, eyes, bones, central nervous system and internal organs. While S. aurantiacum has a minor role in the colonisation of lungs in Germany and France, in Australia, it comprises approximately one-third of Scedosporium spp. recovered from cystic fibrosis lungs where it may co-exist with other prokaryotic lung inhabitants such as Pseudomonas aeruginosa . However, very little is known about mixed bacterial–fungal interactions or host–fungal interactions in the lungs, all of which may have an impact on disease outcome. Also, the nature of potential virulence factors such as production of particular proteases would require more research. A wide range of molecular diagnostic techniques now available can facilitate rapid and accurate identification of Scedosporium spp. in clinical specimens and environmental samples. However, molecular tools allowing gene overexpression and knockout studies are yet to be fully developed. A draft genome is currently available for S. aurantiacum strain WM 09.24 (CBS136047), an Australian environmental isolate. The emerging genomic tools and metabolic and transcriptomic studies discussed will further advance understanding of the pathogenic mechanisms of members of the genus Scedosporium, including S. aurantiacum .